Les fondements historiques de l'ethnobiologie (1860-1899) - Clément, Daniel (Anthropologica, 2022)
The origin of ethnobiology, defined here as the study of the biological sciences as they are practised by the various ethnic groups studied by ethnology, can be traced to the end of the 19th century when different names were given to its subdisciplines. Those names—applied botany, Aboriginal botany, botanical ethnography, ethnographic conchology, botany, ethno-conchology, plant-lore and, finally, ethno-botany and ethnozoology—appear in a context where Westerners are mostly interested in the economic usage of aboriginal products made out of plant or animal material. The researchers, botanists, zoologists as well as ethnologists, missionaries, adventurers, often work for museums, deny any form of scientific knowledge to indigenous people and, consequently, are more interested in those products which can be used by civilization than in the knowledge of these people they report to be in a savage state.